T helper profile in pregnant women recovered from COVID-19. (September 2022) - Tartaglia, Eleonora; Bordoni, Veronica; Oliva, Alessandra; Vergori, Alessandra; Girardi, Enrico; Antinori, Andrea; Agrati, Chiara; Liuzzi, Giuseppina
Abstract: T helper (Th) cell subsets play distinct and important roles during pregnancy. This work was focused on investigating the Th and cytokine profile in pregnant women recovered from COVID-19. To this aim, the frequency of Th1, Th2, Th17 subsets and the level of associated cytokines were analysed in pregnant women recovered from COVID-19 and in matched non-pregnant women. Principal component analysis highlighted a significant impact of pregnancy on Th profile with an increase of ex-Th17 subset and a parallel decrease of Th1 population. These modulations may participate in both preserving the pregnancy and reducing the risk of severe infection.